Characterization of hemicellulase and cellulase from the extremely thermophilic bacterium Caldicellulosiruptor owensensis and their potential application for bioconversion of lignocellulosic biomass without pretreatment. Issue 1 (December 2015) - Peng, Xiaowei; Qiao, Weibo; Mi, Shuofu; Jia, Xiaojing; Su, Hong; Han, Yejun
Abstract Background Pretreatment is currently the common approach for improving the efficiency of enzymatic hydrolysis on lignocellulose. However, the pretreatment process is expensive and will produce inhibitors such as furan derivatives and phenol derivatives. If the lignocellulosic biomass can efficiently be saccharified by enzymolysis without pretreatment, the bioconversion process would be simplified. The genusCaldicellulosiruptor, an obligatory anaerobic and extreme thermophile can produce a diverse set of glycoside hydrolases (GHs) for deconstruction of lignocellulosic biomass. It gives potential opportunities for improving the efficiency of converting native lignocellulosic biomass to fermentable sugars. Results Both of the extracellular (extra-) and intracellular (intra-) enzymes ofC. owensensis cultivated on corncob xylan or xylose had cellulase (including endoglucanase, cellobiohydrolase and β-glucosidase) and hemicellulase (including xylanase, xylosidase, arabinofuranosidase and acetyl xylan esterase) activities. The enzymes ofC. owensensis had high ability for degrading hemicellulose of native corn stover and corncob with the conversion rates of xylan 16.7 % and araban 60.0 %. Moreover, they had remarkable synergetic function with the commercial enzyme cocktail Cellic CTec2 (Novoyzmes). When the native corn stover and corncob were respectively, sequentially hydrolyzed by the extra-enzymes ofC. owensensis and CTec2, the glucan conversion rates were 31.2 and 37.9 %, which were 1.7- and 1.9-fold of each control (hydrolyzed by CTec2 alone), whereas the glucan conversion rates of the steam-exploded corn stover and corncob hydrolyzed by CTec2 alone on the same loading rate were 38.2 and 39.6 %, respectively. These results show that hydrolysis by the extra-enzyme ofC. owensensis made almost the same contribution as steam-exploded pretreatment on degradation of native lignocellulosic biomass. A new process for saccharification of lignocellulosic biomass by sequential hydrolysis is demonstrated in the present research, namely hyperthermal enzymolysis (70–80 °C) by enzymes ofC. owensensis followed with mesothermal enzymolysis (50–55 °C) by commercial cellulase. This process has the advantages of no sugar loss, few inhibitors generation and consolidated with sterilization. Conclusions The enzymes ofC. owensensis demonstrated an enhanced ability to degrade the hemicellulose of native lignocellulose. The pretreatment and detoxification steps may be removed from the bioconversion process of the lignocellulosic biomass by using the enzymes fromC. owensensis .